Pengaruh Media Sosial Marketing Terhadap Peningkatan Minat Beli Pelanggan Toko Berliian Motor Gunungsitoli - Telaumbanua, Arisanto; Nov Elhan Gea; Emanuel Zebua; Sophia M. Kakisina (LPPM Universitas HKBP Nommensen, 2024)
In the world of business marketing, this is the most crucial or important thing. Business developments have resulted in changes such as changes in the mindset of competitors or business people in maintaining their business. Marketing or marketing is an activity, a series of institutions and processes of creating, communicating, delivering and exchanging deals (offers) that are of value to customers, clients, partners and the general public. This research aims to find out the role of Social Media Marketing in Increasing Customers at the Gunungsitoli Berlian Motor Shop. The research method used is a quantitative research method with a survey approach, researchers also use questionnaires in data collection. Researchers tested the hypothesis using multiple regression analysis techniques and the calculations were assisted using the SPSS (Statistical Program For Social Science) software program version 26. This research found that social media (X) which was accepted and partially had a positive and significant influence on buying interest (Y ) consumers at the Berlian Motor Shop in Gunungsitoli city.